An Explicit Bound for the First Sign Change of the Fourier Coefficients of a Siegel Cusp Form. (2nd April 2014) - Choie, YoungJu; Gun, Sanoli; Kohnen, Winfried
Abstract: We give an explicit upper bound for the first sign change of the Fourier coefficients of an arbitrary nonzero Siegel cusp form F of even integral weight on the Siegel modular group of arbitrary genus g ≥2.